Pengembangan Usaha Butik Pada Masa Pandemi Covid-19 di Wu&Wilson Bandar Lampung - Yudhia, Reginna; Ali Alam, Iskandar (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The purpose of this research is to find out the right business development strategy for the sustainability of the Wu & Wilson boutique and to stabilize revenue at the Wu & Wilson boutique business during the covid-19 pandemic. The analytical method used in this study is a qualitative method where the source of the data obtained is information obtained from interviews with informants. As for some of the informants needed in this study, namely owners, employees, buyers and users of products from the Wu & Wilson boutique. Data collection techniques used are observation, interviews, documentation and questionnaires. The results of this study indicate that Wu&Wilson Boutique Bandar Lampung needs another strategy to develop its business, namely by creating products that are more modern in terms of design and model, increasing fashion collections, providing discounts and attractive promos and being marketed to the public through social media such as Instagram so that it can attract attention and interest higher consumer buy.